2017
DOI: 10.1007/s11356-017-0789-1
|View full text |Cite
|
Sign up to set email alerts
|

Influence of technological and municipal wastewaters on vulnerable karst riverine system, Krka River in Croatia

Abstract: Exceptional natural value of karst rivers, as well as their potential as a source of drinking water supply, contributes to the importance of developing strict environmental protection. Although most of its watercourse is proclaimed national park, Krka River is impacted by technological and municipal wastewaters, which are released without proper purification only 2 km upstream of the park border. In order to assess water ecological status of the Krka River, vulnerability of karst ecosystem and potential threat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 14 publications
2
12
1
1
Order By: Relevance
“…Nichols and Playle (2004) reported the positive influence of increased ambient temperature on Ag accumulation in the liver of O. mykiss, probably due to increased fish metabolic rates at higher water temperatures, whereas the same effect was not observed on Ag elimination; therefore, they found higher Ag concentrations in the liver of O. mykiss kept at higher compared to lower water temperatures. Although water temperatures in autumn and spring samplings are usually comparable (Filipović Marijić et al, 2017), higher hepatic Ag levels in S. trutta in the autumn compared to spring in our study could be explained by the fact that autumn sampling occurred after long period of high summer temperatures.…”
Section: Differences In Total and Cytosolic Metal/metalloid Concentracontrasting
confidence: 51%
See 1 more Smart Citation
“…Nichols and Playle (2004) reported the positive influence of increased ambient temperature on Ag accumulation in the liver of O. mykiss, probably due to increased fish metabolic rates at higher water temperatures, whereas the same effect was not observed on Ag elimination; therefore, they found higher Ag concentrations in the liver of O. mykiss kept at higher compared to lower water temperatures. Although water temperatures in autumn and spring samplings are usually comparable (Filipović Marijić et al, 2017), higher hepatic Ag levels in S. trutta in the autumn compared to spring in our study could be explained by the fact that autumn sampling occurred after long period of high summer temperatures.…”
Section: Differences In Total and Cytosolic Metal/metalloid Concentracontrasting
confidence: 51%
“…The association of Co with S. trutta length was negative and rather strong, meaning that higher concentrations were found in smaller specimens. However, this correlation was determined in both sampling campaigns only at the contaminated site, downstream of Knin town (r = -0.659 and -0.720; p<0.01), where Co accumulation in S. trutta liver was significantly higher compared to the reference site (Table 3), same as Co exposure level in the river water (Table 1; Filipović Marijić et al, 2017;Sertić Perić et al, 2017). Therefore, it can be presumed that in the conditions of increased exposure to Co, smaller S. trutta specimens accumulate higher amounts of this metal than the bigger ones.…”
Section: Association Of Total Metal/metalloid Accumulation In Liver Wmentioning
confidence: 89%
“…Based on the previously published data on the physico-chemical water parameters and total dissolved metal levels in the river water (Cukrov et al, 2008;Filipović Marijić et al, 2018), river source was chosen as the reference site, whereas a location downstream of the town of Knin, located 2 km upstream of the northern border of the Krka National Park, was selected as the contaminated site. Krka River is threatened by two known sources of contamination: technological wastewaters of the screw factory and municipal wastewaters of the town of Knin.…”
Section: Study Areamentioning
confidence: 99%
“…The wastewaters are released without a proper treatment into the river watercourse just 2 km upstream of the border of the Krka National Park. Krka River water analyses conducted upstream and downstream of the wastewater discharge have shown that metal/metalloid concentrations were increased at the affected site Filipović Marijić et al, 2018;Sertić Perić et al, 2018). Dissolved metals in water with the highest concentrations at the anthropogenically impacted site were Fe, Li, Mn, Mo, Sr, Rb and Ca and among them Fe and Mn are metals specific for technological wastewaters and often used in the manufacture of iron and steel alloys, and manganese products Filipović Marijić et al, 2018;Sertić Perić et al, 2018).…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation